The American Security Model and Its Influence over European Social and Juridic Values - Martínez Quirante, Roser (PRAWO i WIĘŹ, 2022)
The author describes the evolution from the USA individual-centric state towards the administrative and regulatory one. The author examines the very different models of security for the USA and Europe and its influence over European social and juridic values.